The Creep Model of the Anchorage Structure and the Time-Dependent Reliability Analysis - Wang, Jun; Liang, Qiao; Duan, Jian (Frontiers in Earth Science, 2020)
The anchorage structure is a complex bearing system with undetermined failure modes. According to the component characteristics, we established the segmented diagram for the bearing characteristics and the bearing structure at the anchorage segment. In addition, we described the failure patterns of the subsystems of the anchorage structure and further established the series model for the bolted reinforced system. Moreover, according to the total displacement and the time-dependent deformation characteristics of the bolt, we established a nonlinear creep model to analyze the viso-plastic deformation characteristics of the M-C element. Furthermore, considering the shear strength of the anchored soil, we assumed that the cohesion and the internal friction angle were random variables obeying the Weibull distribution. Using the modified first-order second-moment method (JC method), we obtained the analytic expression of the time-dependent index of the anchorage system. The calculation shows that the variable coefficients of the cohesion and the internal friction angle are exponentially and linearly related to the reliability index, respectively. Simultaneously, the reliability index is exponentially related to time.